Prevalence and correlates of sleep problems among elderly Singaporeans. Issue 1 (27th January 2016) - Sagayadevan, Vathsala; Abdin, Edimansyah; Binte Shafie, Saleha; Jeyagurunathan, Anitha; Sambasivam, Rajeswari; Zhang, Yunjue; Picco, Louisa; Vaingankar, Janhavi; Chong, Siow A.; Subramaniam, Mythily
Abstract : Background: The current study examined the prevalence and correlates of sleep problems among elderly Singaporeans. Methods: Data were taken from the Well‐being of Singapore Elderly study, a cross‐sectional, epidemiological survey conducted among Singapore residents aged 60 years and above ( n = 2565). Respondents were screened for sleep problems through a series of questions in the Geriatric Mental State examination. Details on sociodemographic characteristics, physical activity, cognition, disability, chronic physical conditions, and depression were also collected. Logistic regression analysis was used to explore significant associations between sleep problems, sociodemographic characteristics, physical activity, cognition, disability, chronic physical conditions, and depression. Results: Overall, 13.7% ( n = 341) of older adults reported at least one sleep problem. Of those who reported sleep problems, 69.4% experienced sleep interruption at night, 48.9% reported having difficulty falling asleep, 22.3% reported early morning awakening, and 11.4% had all three problems. Elderly with sleep problems were significantly more likely to have a range of chronic physical conditions and depression and were also significantly less likely to be physically active. Older adults with at least one sleep problem reported significantly greater disability compared to those with no sleep problems. Conclusion: The high probability of comorbid chronic conditions as well as higher disability among those with sleep problems makes this an important area of research.